OPPORTUNITY FOR AGRO ENTREPRENEUR IN DEVELOPING AGRO INITIATIVE IN ISLAMIC BANKING IN MALAYSIA - Muhammad Ridhwan B. Ab. Aziz. (Journal of Animal and Plant Sciences, 2011)
This article tries to examine the concept of agriculture and agribusiness in Islam and financing facilities available for the agriculture sector provided by the Islamic Banking in Malaysia. Thus, this article will be divided into two sections. The first section begins with the exploration of agriculture and agribusiness in Islam, whilst the second section in this article will discuss Islamic financing facilities in agriculture provided by the local Islamic Banks. All financing facilities offered by the banks will be explained in details in this section as well as the relevant products with respect of financial assistant to agro entrepreneurs in developing their projects. The methodology of this research is through documents analysis as well as field study with the officers of the selected Islamic Banks.
Keywords: Agriculture; Agribusiness; Islamic Banks